Microstructure and mechanical properties of titanium aluminum carbides neutron irradiated at 400–700 °C. Issue 6 (June 2017) - Ang, Caen; Parish, Chad M.; Shih, Chunghao; Silva, Chinthaka; Katoh, Yutai
Abstract: This work reports the first mechanical properties of Ti3 AlC2 -Ti5 Al2 C3 materials neutron irradiated at ∼400, 630 and 700 °C at a fluence of 2 × 10 25  n m −2 (E > 0.1 MeV) or a displacement dose of ∼2 dpa. After irradiation at ∼400 °C, anisotropic swelling and loss of 90% flexural strength was observed. After irradiation at ∼630–700 °C, properties were unchanged. Microcracking and kinking-delamination had occurred during irradiation at ∼630–700 °C. Further examination showed no cavities in Ti3 AlC2 after irradiation at ∼630 °C, and MX and A lamellae were preserved. However, disturbance of (0004) reflections corresponding to M-A layers was observed, and the number density of line/planar defects was ∼10 23  m −3 of size 5–10 nm. HAADF identified these defects as antisite TiAl atoms. Ti3 AlC2 -Ti5 Al2 C3 shows abrupt dynamic recovery of A-layers from ∼630 °C, but a higher temperature appears necessary for full recovery.